2007
DOI: 10.2193/2006-015
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response of Working African Elephants to Transportation and Safari Adventures

Abstract: : African elephants (Loxodonta africana) are intensively managed in southern Africa and are routinely translocated between reserves. Domesticated elephants are used for elephant‐back safaris and interactions with guests. Understanding how elephants respond to such activities is critical because of welfare issues associated with both humans and elephants. We investigated the stress response (i.e., fecal glucocorticoid metabolite secretion [FGM]) of working elephants in Letsatsing Game Reserve, South Africa, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 15 publications
7
64
2
1
Order By: Relevance
“…The effect was apparent in corticosterone levels for longer than from behavioural assays (Burke et al, 2008). Although there was increased stress throughout the population during these disturbances, the levels of corticosterone were still much lower than those associated with natural stress events, for example during thunderstorms (Millspaugh et al, 2007).…”
Section: Short-term Effects On Remaining Elephants (Stress)mentioning
confidence: 80%
See 1 more Smart Citation
“…The effect was apparent in corticosterone levels for longer than from behavioural assays (Burke et al, 2008). Although there was increased stress throughout the population during these disturbances, the levels of corticosterone were still much lower than those associated with natural stress events, for example during thunderstorms (Millspaugh et al, 2007).…”
Section: Short-term Effects On Remaining Elephants (Stress)mentioning
confidence: 80%
“…In another more recent study it was shown that transport of captive elephants did increase their secretion of glucocorticoids. However, the proximity of other known herd members and allowing them to interact, did decrease their stress levels (Millspaugh et al, 2007). Such information may assist translocation teams' efforts to reduce stress in future translocations.…”
Section: Minimising and Monitoring Stress Imposed By Capture Operationsmentioning
confidence: 92%
“…For validation of a GC assay, we used the stressful situation of sedation and transportation, which is well-known to elicit increased GC output (e.g. [40,42,72]. A native cortisol assay (described by Palme and Möstl [50]) and two cortisol metabolite assays (11b-hydroxyetiocholanolone, described by [16], and 11-oxoetiocholanolone, described by Möstl et al [42]), were tested for their reliability in reflecting adrenocortical activity from orangutan fecal samples.…”
Section: Hormone Analysis and Validation Of Fecal Glucocorticoid And mentioning
confidence: 99%
“…However, there are potential drawbacks with the translocation of any wild animal, and one of these is the stress associated with capture, transportation, and post-translocation adjustment (Goymann et al 1999;. For example, Millspaugh et al (2007) recently demonstrated that faecal glucocorticoid metabolite (FGM) concentrations of African elephants living in a hands-on environment increased as a response to transportation.…”
Section: Introductionmentioning
confidence: 99%